SISTEM INFORMASI PENJADWALAN MENGAJAR MENGGUNAKAN METODE ALGORITMA GENETIKA PADA SMK 10 NOPEMBER JOMBANG - Suprayitno/mak Yunus Suprayitno/amak yunus (Jurnal Fakultas Teknologi Informasi, 2015)
ABSTRACTSuprayitno, Parsun. 2014.  Teaching Sheduling Information System Using Genetic Algorithms in SMK 10 Nopember Jombang. Department of Information System, Faculty of Information Technology Kanjuruhan University of Malang. Preceptor: Amak Yunus, S.Kom, M.Kom.Keyword : Information System, Scheduling , Genetic Algorithm.Scheduling process at SMK 10 November Jombang is to combine the components of teachers, subjects, classes and time. There are schedules  conflict as well as the  problem of  teachers  demands not be able to  teach  at a particular time. It is necessary  to build  scheduling information system using Genetic Algorithm, which simulates the process of evolution to produce the chromosomes of each population randomly,  then  chromosomes  replicate in  accordance  to  laws of evolution be tranformated into  prime chromosome. This chromosome produces a solution of the issues raised.The conclusion of this system; it  can arrange the overall timetable, schedule conflicts can be resolved and demand of teachers  not be able    teach on certain days and hours can be fulfilled